A new angiographic scoring for grading the difficulty of recanalization for symptomatic non-acute middle cerebral artery occlusions - Cao, Jie; Zhu, Xucheng; Liu, Sheng; Zhang, Yunfeng; Yin, Congguo; Zhong, Chongke; Mo, Yi; Xuan, Jinggang; Chen, Ronghua; Zhou, Chun; Huang, Guoxiang; Xia, Wenqing; et al. (Frontiers in Neuroscience, 2024)
BackgroundEndovascular recanalization is a feasible option for treating symptomatic non-acute middle cerebral artery occlusion (MCAO) patients. Hence, we aimed to establish a new angiographic scoring to grade the recanalization difficulty of MCAO to determine the suitable patients for endovascular treatment.MethodsWe retrospectively analyzed a total of 113 consecutive recurrent symptomatic non-acute MCAO patients who underwent endovascular recanalization from July 2015 to August 2021 in four Chinese comprehensive stroke centers. All patients were reappraised using a new angiographic scoring based on the stump morphology, the MCA occlusion length, MCA bend, and the distal vascular bed of MCAO. We used the final results to establish the patients’ outcomes.ResultsThe total successful recanalization and perioperative complication rates were 83.2% (94/113) and 15.9% (18/113), respectively. No deaths occurred within 30 days. Moreover, 96.9, 90, 87.5, 52.6, and 50% of the patients achieved recanalization with scores of 0, 1, 2, 3, and 4 (p < 0.001), respectively. However, the perioperative complication rate showed the opposite trend. (3.1% vs. 7.5% vs. 6.3% vs. 52.6% vs. 50%; p < 0.001). The median time of successful microwire crossing of the occlusion lesion (TMO) in the score 0 group was shorter than the other groups (2 min, 9 min, 8.5 min, 14 min, and 20 min; p < 0.001). When a score of 2 was used as the optimal cut-off point, the sensitivity and specificity were 86.2 and 63.2%, respectively.ConclusionThe new angiographic scoring can effectively predict the successful recanalization rate, perioperative complication rate, and TMO of endovascular recanalization for non-acute MCAO. It can also be used as an effective clinical evaluation tool to determine the suitable non-acute MCAO patients for recanalization, especially with a score ≤ 2.